Aplikasi blood smart: Media pembelajaran biologi berbasis android di era revolusi industri 4.0 - Nurul Asikin; Nevrita Nevrita; Wihelmina Noni (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
The learning media based on android for biology have not been used optimally in the era of the industrial revolution 4.0. The research objective was to determine the feasibility of blood smart applications as a learning media based on android for biology in the era of the industrial revolution 4.0. The type of research used is research and development with the Thiagarajan Four-D model which includes define, design, and develop. The research instrument used a material expert questionnaire, media expert, teacher practicality questionnaire, and student practicality questionnaire given to 30 students. The research data is qualitative in the form of suggestions and comments from experts and teachers which are analyzed descriptively, while quantitative data is processed into interval data using a Likert scale. The results showed that the blood smart application was declared valid in the media aspect (95.2%), the material aspect (87.5%). The practicality of the blood smart application by the teacher was 95% (very practical criteria), and the practicality by students was 91.8% (very practical criteria). Thus, the blood smart application is suitable for use as a learning media based on android for biology in the era of the industrial revolution 4.0.